2016
DOI: 10.1161/atvbaha.115.306871
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Destabilizes Coronary Plaques in Watanabe Heritable Hyperlipidemic Rabbits

Abstract: Objective Increased plasma concentrations of angiotensin II (Ang II) have been implicated in many cardiovascular diseases such as atherosclerosis, aortic aneurysms and myocardial infarction in humans. However, it is not known whether high levels of plasma Ang II affect coronary plaque stability and subsequent myocardial infarction. The current study was designed to examine whether elevated plasma Ang II can directly induce coronary events such as acute coronary syndrome. Approach and Results To examine the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…It is worth noting that in the HTN group, the advanced lesions contained calcified foci but lacked typical necrotic/lipid cores or plaque rupture. These features are different from AngII-infused WHHL rabbits, in which coronary erosion/rupture can be induced [17]. On the other hand, HTN WHHL rabbits exhibited a higher frequency of intraplaque hemorrhages in the aorta [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that in the HTN group, the advanced lesions contained calcified foci but lacked typical necrotic/lipid cores or plaque rupture. These features are different from AngII-infused WHHL rabbits, in which coronary erosion/rupture can be induced [17]. On the other hand, HTN WHHL rabbits exhibited a higher frequency of intraplaque hemorrhages in the aorta [30].…”
Section: Discussionmentioning
confidence: 99%
“…BP and heart rate were examined every for 4 weeks during the experiment as described previously [16, 17]. To avoid environmental stress, BP measurements were conducted in a separate room.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the authors also describe some cases of plaque erosion as a cause of myocardial infarction. If shown that the response to pharmacological treatment mirrors what we see in humans, then the model described by Li et al 54 would constitute a compelling model for testing of new, potentially plaque-stabilizing drugs that could prevent myocardial infarction.…”
Section: Animal Models Of Plaque Rupture and Erosionmentioning
confidence: 95%
“…Importantly, it reflects pharmacological effects of drugs that are known to stabilize plaques in humans. 47 Recently, Li et al 54 have reported coronary plaque rupture/erosion in Watanabe Heritable Hyperlipidemia rabbits infused with angiotensin II. The authors provide strong histological evidence of plaque rupture, including fibrous cap break, luminal thrombosis, intraplaque hemorrhage, and a high percentage of mortality caused by myocardial infarction.…”
Section: Animal Models Of Plaque Rupture and Erosionmentioning
confidence: 99%
“…A small (1 cm) cut was made in the mid scapular region and an osmotic pump was implanted (Alzet, Cupertino, CA, USA), and subsequently the wound was sutured. Pumps with a release rate of 160 ng/min per day for 6 weeks, were loaded with a high-dose of AngII dissolved in saline [59,60]. Pumps were kept in the animals for the duration of the experimental treatment.…”
Section: Angii Administration and Experimental Proceduresmentioning
confidence: 99%